(untitled) (Global Journal of Human-Social Science, 2014)
This paper sought to highlight the life and work of Joseph Merinyo, using historical-biographical and literature analysis. Serving the society as a houseboy, clerk, store keeper, interpreter and informant, Joseph Merinyo rose from being a simple villager to a high-profile nationalist and freedom fighterworking closely with local chiefs, foreign researchers and administrators. The main finding of the paper was that Merinyo was a patriot, nationalist, and a frontline activist who unwaveringly fought for social justice and human rights. Key terms (patriot, nationalist, justice, kingmaker, human rights, and diplomacy) were defined according to the context of the paper and it was concluded that hard work, social commitment, and self-sacrifice were virtues which elevated Merinyo to international stature and reputation. Studying people like Joseph Merinyo enables members of the society, the younger generation in particular, understand the legacy of African makers of history. As a challenge and invitation for future research, two recommendations were made. First, it is necessary to study important persons like Joseph Merinyo because such studies help to interpret Africa to the outside world; and second, African heroes and heroines should be studied -not only to satisfy historical curiosity but also to benefit from the immeasurable insights packed in the history of their lives.